Mechanisms of autoimmune-mediated paraneoplastic syndromes: immune tolerance and disease pathogenesis - Pérez-Bucio, César; Behere, Anish; Landegren, Nils (Frontiers in Immunology, 2025)
Paraneoplastic syndromes represent a clinically heterogeneous group of disorders that arise in cancer patients. Although their underlying mechanisms are only partly understood, immune or endocrine mechanisms are believed to play key roles. Autoimmune-mediated paraneoplastic syndromes (AMPS) are typically characterized by the presence of autoantibodies, making their identification important for both AMPS diagnosis and early cancer detection. This review synthesizes emerging insights into the pathogenesis of AMPS, with a particular focus on how genomic instability in cancer cells promotes immune recognition of altered self-proteins. Mechanisms such as ectopic expression, protein modifications (such as isoaspartylation), and gene amplifications can disrupt immune tolerance, leading to autoimmunity. Additionally, chronic inflammation and the formation of tertiary lymphoid structures within the tumor microenvironment contribute to both antitumor immunity and autoimmunity. Immune checkpoint inhibitors (ICIs), have revolutionized cancer treatment by enhancing antitumor immunity, but they can also induce immune-related adverse events (irAEs), some of which mimic AMPS. These irAEs highlight the critical roles of both humoral and cellular immunity in AMPS development. By exploring the relationships between ICI treatment, immune tolerance, and tumor-specific antigens, this review aims to clarify the mechanisms driving AMPS and their dual role in cancer control and immune-mediated disease. Bridging these knowledge gaps may inform the development of novel therapeutic strategies for managing AMPS and in optimizing the use of ICIs in cancer care.